ASSESSING YOGYAKARTA CREATIVE CITY ACCORDING TO CHARLES LANDRYâS CREATIVE CITY INDEX - Y Meinadia S K A, M
Indonesia has joined AEC (ASEAN Economic Community) that makes Indonesia has to compete internationally. Creative economic is believed to be one driving sector that can capture the opportunity of AEC. Therefore creativity and knowledge become an invaluable asset in competition and economic development. Indonesia economic development that relies on the natural resources has reached an overload point due to diminishing natural resources, so that in the long term it is no longer reliable as a source of new economic growth. Over the past decade, Indonesia try to increase competitiveness both in terms of products and human resources to be nation’s competitive advantage. The problems and challenges facing the national economy are also directly faced by the city of Yogyakarta. In the midst of effort to realize quality and sustainable economic development, Yogyakarta city is required to optimize the potential of human resource creativity. The researcher is aimed to know the readiness of Yogyakarta to be a creative city based on Charles Landry’s index, and see the ecosystem of the most potential sub sector creative industry that influenced Yogyakarta in order to reach the goal of creative city. The research method used in this analysis was qualitative and quantitative. Firstly, the researcher defines the index of being creative city by Charles Landry’s creative city index. Every index has four to six statements that can describe the index. The analysis includes survey, observation, and interview of fifty respondents related to the research. The fifty respondents did the questionaire and interview section related to the research topic. The interview has been recorded by the researcher and transcripted verbatim. Benchmarking analysis used a descriptive theory that has been analyze before and in-depth interview. The findings from the analysis is Yogyakarta fulfilled seven out of ten index that are more than moderate level. The seven index that are more than moderate level: Distinctiveness, Openness, Entrepreneurship, Strategic Leadership, Talent Development, Profesionalism, and Communication. However, The Political Public Framework, Placemaking, and Liveability, are index that are still in moderate level. Based on the analysis, Yogyakarta has top three subsectors that influenced the city. Arts, Performing Arts, and Music becomes the most affected subsectors in Yogyakarta. The ecosystem of these three subsectors has already been completed from the create value chain, market, apreciation and archiving. This makes Yogyakarta can develop the leading creative industry subsectors. In addition, these creative industries has been built the ecosystem that sustain the creative economy as an industry and facilitate the citizens interests and works. There are many education infrastuctures, studios, events, and festivals that occurs in Yogyakarta.